(untitled) (Studia Prawnicze / The Legal Studies, 2023)
During the first years after World War Two housing needs of the population of the cities were first of all fulfilled from the resources administered by state organs. The participation of the population in building of houses was rather insignificant. Constantly diminishing housing resources and — on the other hand — grouth of industrial and agricultural production, caused the increase of real incomes of the population and changes in the state policy in the domain of building of houses, so as to include the iniciative and private funds of the population to the degree higher than thus far into the process of building. In order to carry out new haousing policy it was necessary to provide proper land for building, among others, for building of one family houses. This problem was to be solved by the law of July 6, 1972 on land designated for building one family houses and individual cultivation, and on division of real properties in towns and settlements (Journal of Laws n° 27 entry 192, changes in the Journal of Laws of 1973 n° 48 entry 282). This article aims at presenting all the problems pointed out in the title, and especially the problem of interpretation of several laconic provisions of te law of July 6, 1972. The article brings the reader’s attention to the fact that the law does not regulate all the issues connected with urban building because beyond its scope there remain some important general problems of administration of land in towns, problems of spatial planning, carrying out of industrial investments, building for communal purposes, construction of houses for many families by housing cooperative societies, etc. The article discusses administrative proceedings aimed at designation of land for the purposes of one family houses construction and for individual cultivation by workers of State or cooperative farms, as well as distribution of lots (declaration of preservation of ownership, assignement of lots in ownership or in perpetual usufruct). It also presents judicial proceedings and proceedings before state notarial offices in cases dealing with real properties and decisions designating land for purposes of such building. A critical opinion of the Author on several regulations contained in the law is also presented. Among others this concerns article 8 linea 3 which discriminates co-owners of real properties situated on building land if co-ownership, does not result from succession or cessation of joint property of husband and wife, and article 9 linea 1 which allows to assing a lot only to a young person of age or to a grandchild of the owner of real property which was included into the land designated for building. The final part contains some suggestions as to appropriateness of introducing some changes into the provisions now binding, also as far a appropriateness of regulating all the issues concerning land in the towns i one legal act.